Role Of Elementary School In Sport Development In Wonosobo Distric, Central Java: Peran Sekolah Dasar Dalam Pengembangan Olahraga Di Kabupaten Wonosobo Jawa Tengah - Jazuli, Rodli (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to analyze the development of wonosobo district sports which is seen from the role of elementary school. This research is included in the type of public policy analysis research with a qualitative research approach. Where data collection techniques use observation, interview, document study and policy analysis techniques using the exercise development program implementation index. The results showed that the index value was not so high, it showed that the role of physical education at the elementary school level in Wonososbo Regency had not been implemented well, of course because of the lack of active role of schools in increasing the hobby of exercising from an early age, this had an impact on the lack of sports human resources in the long run. The conclusion of this study is that Wonosobo Regency is still in the low category because the total human resource index of Wosnosobo Regency is still below the national index number.